PRAKTIK PENGUNGKAPAN ASPEK TATA KELOLA PERUSAHAAN DALAM LAPORAN TAHUNAN DAN RELEVANSINYA BAGI INVESTOR (STUDI PADA PERUSAHAAN PUBLIK SEKTOR MANUFAKTUR) - Wiwik Utami (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2005)
The objectives of this research are to find out empirical evidence of (1) the value disclosures rank of the corporate governance disclosures to investor’s decisions, and (2) the impact of corporate governance disclosures on stocks price and stock transactions.The population of this study was listed companies in the manufacturing sector at the Jakarta Stock Exchange, and the sample was determined based on the following criteria: (a) the annual report ended 31 December, and (b) book value of equity is positive. There werw 92 companies meeting the criteria. Data analysis was carried out in terms of pool cross-section covering annual report during 2001-2002. Corporate governance disclosures were measured by score based on investment manager opinion. The stock price and the transaction volume were measured based on average price and volume for three days observation. The research hypothesis were tested using multi regression with earnings per share and book value per share as control variables.The results of this research show that (1) disclosures of non financial performance and the background of independence commissioner and directors are the most relevance to investor’s decisions, (2) disclosures of corporate governance have significant impact on stock price and stock transactions.